The Factors Affecting the Utilization of Tetanus Toxoid (TT) Immunization Program Services Among Prospective Brides in the City of Pematangsiantar - Arini Fajriani; Rapotan Hasibuan; Eliska Eliska (Eduvest - Journal of Universal Studies, 2024)
In 2023, there will be 454 prospective brides and grooms in the city of pematangsiantar with a total of 454 female brides and grooms. Based on Tetanus Toxoid (TT) immunization, in 2023 the target number of non-pregnant women of childbearing age is 43.333 with the number immunized being 351 with a percentage of 0,81%. This shows that Tetanus Toxoid (TT) immunization among women of childbearing age and prospective brides in Pematangsiantar City is still very low. The aim of this research is to determine the relationship between factors in the utilization of Tetanus Toxoid (TT) immunization program services among prospective brides in Pematangsiantar city. The type of research used is quantitative cross sectional design. The research was conducted in the city of pematangsiantar. The population was 454 female cats, the sample was 48 people, the sample was obtained using the lemeshow formula. Data analysis is univariate analysis and bivariate analysis (chi-square test) using the SPSS application. The result of the reseach show that variables related to Tetanus Toxoid (TT) immunization in prospective brides are Employment (p=0.311), Education Level (p=0.131), Knowledge (p=0.035), Attitude (p=0.031), Confidence in Health Services (p=0.933) and Ease of Information (p-value= 0.000). The most dominant variable related is ease of information. Conclusion in this study there are 3 factors related to the Tetanus Toxoid (TT) immunization program, namely Knowledge, Attitude and Ease of Information. The benefit of this research can be used as input in order to improve the quality of health service for the community.